Empowering Arthritis Patients: Optimized Drug Delivery through Piroxicam Microcapsule-Embedded Scaffold Implants via Box-Behnken Experimental Design - Kumar, Sampath; Mohan, Mothilal (Pharmaceutical Nanotechnology, 2025)
BackgroundThe necessity for extended drug discharge to alleviate pain without adverse effects underscores the importance of innovative drug delivery systems. Achieving sustained pain relief without compromising patient safety is a critical objective in healthcare. By extending the duration of drug action while suppressing side effects, such systems offer enhanced therapeutic outcomes and improved patient quality of life.ObjectiveThis study endeavors to develop and appraise an innovative implantable drug delivery system by integrating NSAID-loaded gelatin microcapsules into a gelatin scaffold designed to augment drug delivery efficiency and sustain drug release.MethodsPiroxicam-loaded microcapsules with a 1:1 ratio of poly lactic acid and poly lacto glycolic acid showed smaller particle size, good yield, entrapment efficiency, and discharge. They were selected to make gelatin scaffolds with Box Behnken Design using Design Expert software for optimization. The better scaffolds were made in the form of rod-shaped sub-dermal implants. The primary focus of the investigation was the evaluation of critical parameters, specifically entrapment efficiency and drug discharge properties as dependent variables.ResultsMicrocapsules with a 1:1 ratio of PLA and PLGA showed smaller particle sizes, good yield, entrapment efficiency, and discharge. Notably, the Design Expert-driven optimization yields highly favorable results. Furthermore, the scaffolds loaded with microcapsules exhibited favorable physicochemical assets, including drug discharge, for an extended period, underscoring their versatility for drug delivery.ConclusionBy employing Design Expert software for optimization, the study demonstrates promising results, particularly in sustained pain management for arthritis, potentially improving therapeutic outcomes and patient quality of life. The study concludes that the prepared implants (holding scaffolds impregnated with piroxicam-loaded microcapsules) can be promising for relieving arthritis all day.
Keywords: piroxicam